PERSEPSI IBU RUMAH TANGGA MENGENAI KASUS VOICE PHISHING DI KABUPATEN CIREBON - Gani, Julia; Chamidah, Nurul; Aziza, Dina Kholis (Cahaya Ilmu Bangsa, 2025)
This research aims to determine the perceptions of housewives in Cirebon Regency regarding voice phishing, which is a mode of telephone fraud that is currently widespread. Using qualitative research methods, this research systematically describes and analyzes the facts and characteristics of these perceptions. Housewives as research subjects were chosen because they are considered a group that is vulnerable to voice phishing cases, due to the main factor, namely, a lack of understanding of information and communication technology. Data collection was carried out through in-depth interviews, observation and documentation of housewives who had been victims of voice phishing. The research results show that the majority of housewives in Cirebon Regency have a low understanding of voice phishing techniques and modes. This is caused by a lack of digital literacy and awareness about the dangers of cybercrime. Respondents expressed that they felt worried and unsafe when using telecommunications devices due to the increasing risk of fraud. This research identified several factors that influence housewives' perceptions and vulnerability to voice phishing, including low digital literacy, lack of access to information, and high trust in unknown callers. This research also underlines the importance of education and counseling regarding digital security as an effort to prevent voice phishing among housewives. The conclusion of this research emphasizes that prevention efforts such as increasing digital literacy and educational campaigns regarding voice phishing need to be increased to protect housewives from the risk of telephone fraud. With a better understanding of this method, it is hoped that housewives in Cirebon Regency can be more alert and protect themselves from the threat of voice phishing.